Synthesis and properties of 2-(4-phenyl-5-(((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)methyl)-1,2,4-triazole-3-yl)thio)ethanoic acid and its salts - A. S. Hotsulia; S. O. Fedotov (Zaporozhye State Medical University, 2020)
Analysis of the literature over the past decade has shown that the chemistry of 1,2,4-triazole and 1,3,4-thiadiazole attracts considerable interest from scientists around the world because of the many valuable properties of compounds of this class. Bibliosemantic analysis shows that the nuclei of 1,2,4-triazole and 1,3,4-thiadiazole are fragments of a number of known drugs and biologically active compounds. That is why the synthesis and study of physical-chemical, biological properties of salts and acids containing these heterocyclic fragments are quite relevant both from a theoretical and practical point of view. The aim of the work was to targeted synthesis of 2-((4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)methyl)-1,2,4-triazole-3-yl)thio)ethanoic acid and its salts, as well as the establishment of physical-chemical properties of the synthesized compounds. Estimation of the biological potential of the obtained compounds by molecular modeling method. Materials and methods. 4-Phenyl-5-(((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)methyl)-1,2,4-triazole-3-thiol, which was synthesized by the classical method described in earlier works, was used as a key intermediate. The reaction of the corresponding thiol with sodium monochloroacetate in aqueous medium and subsequent acidification with ethanoic acid gave the target acid. Inorganic salts of 2-((4-phenyl-5-(((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)-methyl)-1,2,4-triazole-3-yl)thio)ethanoic acid was synthesized by the reaction of the acid with sodium hydroxide, potassium hydroxide, magnesium oxide, calcium carbonate or zinc sulfate in an aqueous medium. For analysis, the salts obtained were purified by crystallization from methanol. Organic salts of 2-((4-phenyl-5-(((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)-methyl)-1,2,4-triazole-3-yl)thio)ethanoic acid was obtained by the interaction of the corresponding acid with organic bases (ammonia, diethylamine, diethylmonoethanolamine, morpholine, piperidine) in propan-2-ol followed by evaporation of the solvent. For analysis, the synthesized substances were purified by crystallization from a mixture of water - propan-2-ol (1: 1). Results. During the work, the method of obtaining 2-((4-phenyl-5-(((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)methyl)-1,2,4-triazole-3-yl)thio)ethanoic acids was optimized. The role of the reaction medium at this stage was played by water. The conditions of the synthesis of organic and inorganic salts of the specified acid, their structure, and physical-chemical properties were established. The biological potential was preliminarily assessed with molecular docking. Conclusions. As a result of synthetic studies, 11 new, previously undescribed compounds were obtained. The structure, composition and individuality of the synthesized substances was confirmed by a set of the latest physical-chemical methods of analysis.